An exploratory study of marketing in social networking sites Facebook and the advantages to the business - Yusof, Nur Ain; Romle, Abd Rahim; Mohd Kamal, Mohd Khirul Azwan; Othman, Sarimah; Mohd Yusof, Muhammad Suhaimi; Azidin, Siti Sarah (ISLAMIC WORLD Network for Environmental Science and Technology (IWNEST Publisher), 2015)
Background: The application of Web 2.0 has attain social networks users to communicate, share knowledge, review and rate products or services. Apparently, with the astounding popularity of Facebook as social networking, businesses try to gain attention from users by starting their marketing strategy.Some of people that doing sole business do not have organizations and only do online business by utilize Facebook as medium to market their product.On the other hand established company might use Facebook as complement to their traditional marketing to positioning their product brand among Facebook users.Therefore, this paper represents an exploratory effort to identify Facebook as marketing tools because it holds a potential success for businesses expand their market.